TeV gamma-ray sensitivity to velocity-dependent dark matter models in the Galactic Center - Montanari, Alessandro; Macias, Oscar; Moulin, Emmanuel (Physical review, 2023)
The center of the Milky Way is a prime site to search for signals of dark matter (DM) annihilation due to its proximity and expected high concentration of DM. The amplification of the dispersion velocity of DM particles in the Galactic Center (GC), caused by baryonic contraction and feedback, makes this particular region of the sky an even more promising target for exploring velocity-dependent DM models. Here we demonstrate that current GC observations with the H.E.S.S. telescope, presently the most sensitive TeV-scale gamma-ray telescope in operation in this region of the sky, set the strongest constraints on velocity-dependent annihilating DM particles with masses above 200 GeV. For p-wave annihilations, they improve the current constraints by a factor of ∼4 for a DM mass of 1 TeV. For the spatial distribution of DM, we use the results of the latest FIRE-2 zoom cosmological simulation of Milky Way-size halos. In addition, we utilize the newest version of the galprop cosmic-ray propagation framework to simulate the Galactic diffuse gamma-ray emission in the GC. We have found that p-wave (d-wave) DM particles with a mass of approximately 1.7 TeV and annihilating into the W+W− channel exhibit a velocity-weighted annihilation cross-section upper limit of 4.6×10−22 cm3 s−1 (9.2×10−17 cm3 s−1) at a 95% confidence level. This is about 460 (2×106) times greater than the thermal relic cross section for p-wave (d-wave) DM models.